PENGARUH KECUKUPAN MODAL TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH - Nugrahanti, Pipin; Tanuatmodjo, Heraeni; Purnamasari, Imas (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - The purpose of this research are to descript of capital adequacy, the descript of profitability, while the purpose of this study is to determine the description of perception capital adequacy to profitability in Islamic bank.Design / methodology / approach - Method in this research used descriptive and verification methods. Data that used are secondary data Â of each Islamic Bank period 2012-2016 with analysis technique using simple linear regression. Sampling in this research use purposive sampling.Findings - The result showed that the capital adequacy level has a positive effect to profitability.Originality -The difference of this research with previous research is on research object, population and research sample, research period, measuring instrument and research result.